A Novel Application of Digital Microscope for Microsurgery Training - Sayadi, Lohrasb R.; Fligor, Jennifer E.; Couchois, Sean; Evans, Gregory R. D.; Widgerow, Alan D.; Lanier, Brock (Journal of Reconstructive Microsurgery Open, 2020)
Background Time spent under the microscope is often a limiting factor as plastic surgery residents work toward proficiency in microsurgery. This study describes and assesses a novel application of a digital microscope compatible with smart devices which can consistently and reliably magnify microsurgical fields.Methods A digital microscope was used to display an “operating” field on a tablet device. Two junior plastic surgery residents participated in multiple training sessions. During each session, residents completed two sessions of a knot-tying task and a chicken vessel anastomosis task. The sessions were recorded on the tablet, photographed, and graded by an experienced microsurgeon utilizing three standardized microsurgery training scales (OWOMSA, OSATS, and Global scale) for evaluation. Between sessions, the residents received feedback from the experienced microsurgeon.Results Statistically significant improvements (p < 0.05) in microsurgical technique were observed across 16 areas assessed by the standardized evaluation scales. Additionally, the residents' surveys suggest favorable attitudes toward the digital microscope and its value as a training device.Conclusion Traditional operating microscopes present considerable barriers for effective microsurgical training. The digital microscope analyzed in the present study provides solutions to several of these barriers: it is economical, lightweight, portable, and can be set up by the trainee on any flat surface; photographing and recording capabilities via the connected tablet device make the digital microscope setup optimized for education. Our study demonstrates measurable improvements in trainee's skills with use of—as well as favorable trainee attitudes toward—the digital microscope, which could present a valuable addition to plastic surgery education.
Keywords: microsurgery; digital; education